A sterol-binding protein integrates endosomal lipid metabolism with TOR signaling and nitrogen sensing - Mousley, Carl; Yuan, P.; Gaur, N.; Trettin, K.; Nile, A.; Deminoff, S.; Dewar, B.; Wolpert, M.; MacDonald, J.; Herman, P.; Hinnebusch, A.; Bankaitis, V. (2012)
Kes1, and other oxysterol-binding protein superfamily members, are involved in membrane and lipid trafficking through trans-Golgi network (TGN) and endosomal systems. We demonstrate that Kes1 represents a sterol-regulated antagonist of TGN/endosomal phosphatidylinositol-4-phosphate signaling. This regulation modulates TOR activation by amino acids and dampens gene expression driven by Gcn4, the primary transcriptional activator of the general amino acid control regulon. Kes1-mediated repression of Gcn4 transcription factor activity is characterized by nonproductive Gcn4 binding to its target sequences, involves TGN/endosome-derived sphingolipid signaling, and requires activity of the cyclin-dependent kinase 8 (CDK8) module of the enigmatic “large Mediator” complex. These data describe a pathway by which Kes1 integrates lipid metabolism with TORC1 signaling and nitrogen sensing.